Clinical utility of an immunoglobulin A‐based serological panel for the diagnosis of chronic enteropathy in dogs. (28th January 2023) - Langlois, Daniel K.; Pritchard, Jessica C.; Tolbert, M. Katherine; Jergens, Albert E.; Block, Gary; Hanzlicek, Andrew S.; Jaffey, Jared A.; Steiner, Jörg M.; Marsilio, Sina; Jablonski, Sara A.
Abstract: Background: A panel of IgA‐based serologic assays might aid in the diagnosis of chronic enteropathy (CE) in dogs, a syndrome encompassing conditions such as food‐responsive enteropathy, immunosuppressant‐responsive enteropathy, and inflammatory bowel disease (also referred to as chronic inflammatory enteropathy). However, it is unclear whether these biomarkers discriminate between CE and other types of primary intestinal disorders. Objectives: To evaluate a diagnostic panel that measures serum concentrations of IgA directed against OmpC (ACA), canine calprotectin (ACNA), and gliadin‐derived peptides (AGA) in dogs with well‐characterized intestinal diseases. Animals: Fifty‐five dogs with primary intestinal disease. Methods: Serum ACA, ACNA, and AGA concentrations were measured in 30 dogs with CE and 25 dogs with other intestinal diseases (non‐CE population), including histoplasmosis, parasitism, E . coli ‐associated granulomatous colitis, and lymphoma. Serum IgA concentrations were compared among populations, and sensitivities and specificities were calculated using laboratory‐provided cut‐points. Results: Twenty‐six of 30 (87%) CE dogs and 21 of 25 (84%) non‐CE dogs had abnormal concentrations (intermediate or high) of at least 2 markers; these proportions were not significantly different ( P  = .99). A serum ACA concentration ≥15 EU/mL was 86.7% (95% confidence interval [CI], 69.3%‐96.2%) sensitive and 24.0% (95% CI, 9.4%‐45.1%) specific for CE diagnosis. High AGA concentrations were observed in 16 of 25 (64%) non‐CE dogs. Conclusions and Clinical Importance: The evaluated serologic markers were poorly specific for CE diagnosis, which raises concerns that their use in clinical practice might lead to misdiagnoses and delayed or even detrimental treatments in dogs with non‐CE intestinal diseases.